Analysis of Indonesian Labor Protection Policy from A Globalization Perspective - Rakhul Akbar Maulana; Dody Dwi Kurniawan; Alifa Cesariany Fatchan; Ghifara Alfino Firtiawan; Arif Putra Pamungkas; Rendy Catur Wicaksono; Vanka Lyandova (Proceeding International Conference Restructuring and Transforming Law, 2023)
Globalization has had a significant impact on the world of work and also on labor protection. As foreign investment and exports and imports of goods and services increase, there is a need to protect the rights of workers from being exploited and treated unfairly. In Indonesia, labor protection policies have been regulated in law, but their implementation still faces several obstacles. Therefore, this research aims to analyze Indonesian labor protection policies from a globalization perspective, with a focus on policy implementation and comparison with labor protection policies in other countries. The method used in this research is qualitative with document analysis techniques and interviews with related sources. The data collected was then analyzed using a benchmarking approach to compare labor protection policies in Indonesia with other countries. The research results show that labor protection policies in Indonesia still have several weaknesses in their implementation. There are several factors that cause this, including a lack of awareness and education about labor rights, low levels of community involvement in the policy implementation process, and low sanctions for violations of labor rights. In addition, comparisons with other countries show that there are several policies that can be implemented in Indonesia to improve labor protection, such as minimum wage policies and health protection for workers.